Reliability and validity assessment of the Japanese version of the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU). Issue 3 (June 2015) - Koga, Yuji; Tsuruta, Ryosuke; Murata, Hiroaki; Matsuo, Koji; Ito, Tatsuhiko; Ely, E. Wesley; Shintani, Ayumi; Wakamatsu, Hiroya; Sanui, Masamitsu; Yamase, Hiroaki
Summary Objective Delirium may lead to adverse outcomes in patients with serious conditions, but is often under-diagnosed due to inadequate screening. The Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) is an established method for assessing delirium in the ICU. The validity and reliability of the Japanese version of the CAM-ICU has not, however, been verified, and we undertook this study to verify these parameters. Research methodology CAM-ICU validity and reliability were assessed in two Japanese ICUs. Using the evaluation of the DMS-IV-TR in the psychiatrists group as the standard criteria for delirium diagnosis, we compared the evaluation of the Japanese version of the CAM-ICU between the research nurses group and the staff nurses group. Results According to DSM-IV-TR criteria, the prevalence of delirium was 22.0%, and according to CAM-ICU delirium was found in 22.0% with Research Nurses and 19.5% with Staff Nurses. CAM-ICU sensitivity ratings were 83% and 78%, while their specificity ratings were 95% and 97%, respectively. The Kappa inter-rater reliability was good (κ = 0.85), and Cronbach's alpha coefficient was 0.69 (95% CI: 0.57–0.79). Mean rating time for the CAM-ICU was 2.5–2.8 minutes for Research Nurses and Staff Nurses, respectively. Conclusion The Japanese version of the CAM-ICU has comparable validity and reliability as a delirium assessment tool in surgical patients in two Japanese ICUs. With training, CAM-ICU can be incorporated into daily clinical practice.